THE IMPACT OF REDUCED LOADING DENSITY ON SLAUGHTER CHICKEN TRANSPORT: A HUNGARIAN CASE STUDY - Szőllősi, László; Csorbai, Attila (Applied Studies in Agribusiness and Commerce, 2025)
The European Food Safety Authority (EFSA) has issued a new recommendation regarding the regulation of animal transport, which includes providing more space for animals during transportation. Complying with this recommendation has various economic, environmental, and animal welfare implications. A case study was conducted in cooperation with two slaughterhouses in Hungary to assess the animal welfare, economic, and environmental consequences of reducing bird density during broiler transport. For both companies, data from two consecutive transport trips were analysed: one trip followed the current regulation and practice regarding stocking density, while the other used the lower density recommended by EFSA. Although the two companies used different types of crates and loading methods, the mode of transport, weather conditions, personnel involved in loading and unloading, and measurement procedures were the same. Worse animal welfare indicators (e.g., dead-on-arrival birds, confiscations, limb injuries, bruises) were observed in both cases when loading density was reduced in line with EFSA’s recommendation. Therefore, no clear benefits from an animal welfare perspective could be identified. From an economic standpoint, the implementation of this recommendation would require significant investment, result in higher per-unit transportation costs, and ultimately lead to an increase in poultry meat prices. Furthermore, the environmental impact would also be negative: more transport trips would be needed, leading to increased greenhouse gas emissions and greater water usage for washing vehicles and containers.